Impact of Training on Knowledge and Adoption of Soybean Growers in Maharashtra State - S. K. Deshmukh,; G . Tamilselvi, (Journal of Agricultural Extension Management, 2020)
The research was conducted in ten selected villages of Washim District of Maharashtra to study the impact of training programs conducted by KVK, Karda on knowledge and adoption levels of soybean growers. A sample size comprised of 150 trainees and 150 non-trainees from the KVK operated villages. The results of the study revealed that the trainee farmers had greater knowledge and adoption levels on improved soybean cultivation practices than the non-trainee farmers. The knowledge and adoption indices for various soybean cultivation practices were also more for trainee farmers than their counterparts. Impact of farmers training programme on soybean production technology organized by KVK Washim was found to be 48.15 per cent. This indicates that KVK played a significant role in improving the knowledge and adoption levels among soybean growers